Respuesta :

Answer:

y = 2 ± [tex]\sqrt{x^2 - 4x + 4 + C}[/tex]

Step-by-step explanation:

Solve using separable equations

First put x and dx on the same side and do the same for y

(y-2)dy = (x-2)dx

Now you can integrate

[tex]\frac{x^2}{2} +2x + C1 = \frac{y^2}{2} +2y\\[/tex] + C1

Now we depending on how what ur instructor wants you may need to give exact solutions. We can do this by solving he quadratic equation for Y

Doing this you get:

y = 2 ± [tex]\sqrt{x^2 - 4x + 4 + C}[/tex]

Note C's were simplified.